Odpowiedzi

Najlepsza Odpowiedź!
2010-02-16T03:03:04+01:00
A) 2√6 = √4*√6=√(4*6)=√24
Ponieważ funkcja pierwiastkowa jest funkcją rosnącą, czyli pierwiastek z większej liczby jest większy mamy:
√16<√24<√25, stąd 4<2√6<5

b) 9√10 = √81*√10 = √810
√784 < √810 < √841
28 < 9√10 < 29

c) 4√50 = √16*√50 = √800
√784 < √800 < √841
28 < 4√50 < 29

d) 5√7 = √25*√7 = √175
√169 < √175 < √196
13 < 5√7 < 14

e) 2∛20 = ∛8*∛20 = ∛160
∛125 < ∛160 < ∛216
5 < 2∛20 < 6

f) 5∛7 = ∛125*∛7 = ∛875
∛729 < ∛875 < ∛1000
9 < 5∛7 < 10

g) 8∛2 = ∛512*∛2 = ∛1024
∛1000 < ∛1024 < ∛1331
10 < 8∛2 < 11

h) 2∛5 = ∛8*∛5 = ∛40
∛27 < ∛40 < ∛64
3 < 2∛5 < 4